Peroxisome proliferator-activated receptor alpha plays a crucial role in behavioral repetition and cognitive flexibility in mice - Giuseppe D'Agostino; Claudia Cristiano; David J. Lyons; Rita Citraro; Emilio Russo; Carmen Avagliano; Roberto Russo; Giuseppina Mattace Raso; Rosaria Meli; Giovambattista De Sarro; Lora K. Heisler; Antonio Calignano (Elsevier, 2015)
Background/objectives: Nuclear peroxisome proliferator activated receptor-α (PPAR-α) plays a fundamental role in the regulation of lipid homeostasis and is the target of medications used to treat dyslipidemia. However, little is known about the role of PPAR-α in mouse behavior. Methods: To investigate the function of Ppar-α in cognitive functions, a behavioral phenotype analysis of mice with a targeted genetic disruption of Ppar-α was performed in combination with neuroanatomical, biochemical and pharmacological manipulations. The therapeutic exploitability of PPAR-α was probed in mice using a pharmacological model of psychosis and a genetic model (BTBR T + tf/J) exhibiting a high rate of repetitive behavior. Results: An unexpected role for brain Ppar-α in the regulation of cognitive behavior in mice was revealed. Specifically, we observed that Ppar-α genetic perturbation promotes rewiring of cortical and hippocampal regions and a behavioral phenotype of cognitive inflexibility, perseveration and blunted responses to psychomimetic drugs. Furthermore, we demonstrate that the antipsychotic and autism spectrum disorder (ASD) medication risperidone ameliorates the behavioral profile of Ppar-α deficient mice. Importantly, we reveal that pharmacological PPAR-α agonist treatment in mice improves behavior in a pharmacological model of ketamine-induced behavioral dysinhibition and repetitive behavior in BTBR T + tf/J mice. Conclusion: Our data indicate that Ppar-α is required for normal cognitive function and that pharmacological stimulation of PPAR-α improves cognitive function in pharmacological and genetic models of impaired cognitive function in mice. These results thereby reveal an unforeseen therapeutic application for a class of drugs currently in human use.